Gross and morphometric studies on scapula of Indian elephant - KAPADNIS, P J; GUPTA, S K; KARMORE, S K; JATAV, G P; SHUKLA, B P; SUMAN, A (The Indian Journal of Animal Sciences, 2023)
The main objective of the work was to study gross and morphometry of the scapula of Indian elephant. The fore and hind limbs of the elephant were arranged in an almost vertical position under the body, similar to a pillar or leg of a table rather than being in the angular position seen in many other quadruped mammals to support great weight. The aim of this study was to elucidate the osteological outline on the bones of fore limb in Elephants. Three Indian elephants were used, along with some of the specimens available at the Department of Veterinary Anatomy, College of Veterinary Science and Animal Husbandry, Mhow. It was seen that scapula had two surfaces (lateral and medial), three borders (Cranial border, caudal border and dorsal border) and three angles (cranial, caudal and glenoid). The lateral surface was divided into two unequal fossa by a prominent scapular spine. The height of the scapular spine was lowest in the proximal part, but it increased towards the distal part, and was maximum towards near the acromion process. In the medial surface, a large subscapular fossa was present. The dorsal border was formed by the union of lateral and medial surfaces towards the vertebral column.